Altitudinal Clinal Variation in Wing Size & Shape in African Drosophila melanogaster: One Cline or Many? - Pitchers, William (2012)
Geographical patterns of morphological variation have been useful in addressing hypotheses about environmental adaptation. In particular, latitudinal clines in phenotypes have been studied in a number of Drosophila species. Some environmental conditions along latitudinal clines – e.g. temperature – also vary along altitudinal clines, but these have been studied infrequently and it remains unclear whether these environmental factors are similar enough for convergence or parallel evolution. Most clinal studies in Drosophila have dealt exclusively with univariate phenotypes, allowing for the detection of clinal relationships, but not for estimating the directions of co-variation between them. We measured variation in wing shape and size in Drosophila melanogaster derived from populations at varying altitudes and latitudes across sub-Saharan Africa. Geometric morphometrics allows us to compare shape changes associated with latitude and altitude, and manipulating rearing temperature allows us to quantify the extent to which thermal plasticity recapitulates clinal effects. Comparing effect vectors demonstrates that altitude, latitude and temperature are only partly associated, and that the altitudinal shape effect may differ between Eastern and Western Africa. Our results suggest that selection responsible for these phenotypic clines may be more complex than just thermal adaptation.